PENYULUHAN HUKUM ETIKA DIGITAL PENGGUNAAN MEDIA SOSIAL BAGI SISWA SMA NEGERI 19 BEKASI - Noviriska; Clara Ignatia Tobing (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2022)
Rapid changes in the digital world cause a shift in theway of communicating. People's communication patternschange to fast-paced, short-paced, filled with anonymity, notbound by space and time and strongly influenced by popularculture. This has also resulted in a shift in the norms of decencyand decency in society, especially for teenagers. The absence ofthese politeness norms can have a negative impact on teenagerswhen they are forced to adjust to traditional patterns ofcommunication in society in proper spaces. The partner of thisservice activity is SMA Negeri 19 Bekasi which is located in theMustika Jaya area. and mastery of digital ethical concepts.